Mental health effects of government transfer payments in urban China—An empirical study based on CFPS panel data - Jing Zeng; Yunting Chen; Yafeng Li (Acta Psychologica)
Background: Government transfer payments play a crucial role in redistributing wealth and alleviating relative poverty. However, the mental health effects of government transfers remain to be explored. This study aims to explore the internal mechanisms of the mental health effects of government transfer payments by examining individuals' subjective evaluations and attitudes. Methods: Based on panel data from the 2016 and 2018 China Family Panel Studies (CFPS) urban sample composition (N = 6645), the PSM-DID model was used to investigate the mental health effects of government transfer payments. Based on the calculation of the PSM-DID model, this study examined the effects of social security satisfaction and subjective social status on the mental health effects of government transfer payments through the mediation model and moderation model. Results: The study found that, overall, receiving government transfer payments can significantly reduce the level of individual depression. In examining the mechanism linking government transfer payments and mental health, it was discovered that social security satisfaction partially mediates this relationship. Additionally, subjective social status was identified as a negative moderating factor in this relationship, meaning that the alleviating effect of government transfer payments on depression diminishes as subjective social status increases. Conclusions: Therefore, in future policy optimization, firstly, the size and scope of urban government transfer payments should be expanded to directly improve the living standards of recipients. Secondly, social security programs should be strengthened. Thirdly, implementing the targeted interventions to address disparities in subjective social status should be considered.